Judging offenders: the role of observers' emotions - Wood, Jane L. (UK Data Service, 2010)
This research will conduct two studies. In study one participants' trait empathy will be assessed and then state empathy will be induced in half the sample. The other half will have no emotions induced (controls). Participants will then make judgements regarding: an offender's remorse; responsibility for the offence; likelihood of reoffending; and an appropriate punishment. Study two will duplicate study one but extend it by assigning participants to one of three conditions, where the offender has either: signed a confession and expressed remorse: signed a confession without expressing remorse: neither confessed nor shown remorse. Participants will make the same judgements as in study one. In the second part of study two participants will discuss the case in groups and make group judgements of the offender. The results will tell us whether state or trait emotions influence people's judgements and how trait and state emotions interact. Results will also tell us if an offender's expression of remorse and/or confession interacts with participants' state or trait emotions and affects judgements made individually or in a group. This information will be useful to help identify the potential impact of emotions in legal decisions and how emotions may bias the judicial process.